Acne inversa treated with innovative surgical techniques of wound closure: case report - Matusiak, Łukasz; Bieniek, Andrzej (Dermatology Review/Przegląd Dermatologiczny, 2011)
Introduction . Acne inversa is a recurrent, suppurative disease manifested by abscesses, fistulas and scarring. Many conservative therapies are usually disappointing, and an early surgical intervention often remains the only successful treatment. This condition has a significant impact on the quality of the patient’s life; therefore there is a need for introduction of effective therapeutic modalities at every stage of the disease. Objective . Presentation of two innovative techniques of wound closure after surgical excision of the affected skin areas. Case report . A 42-year-old female patient suffering from acne inversa, treated previously with ineffective methods based on a conservative approach, was operated on with the use of tumescent infiltration anaesthesia and our own surgical techniques such as the “star-like” and “pubic flaps” techniques. Conclusions . Presented data show unequivocally that our own methods of surgical wound closure are highly effective and that a patient with acne inversa can tolerate it well. We encourage the use of these techniques, but choosing the best option requires an individual approach.